Antioxidant properties of selected traditional salads in Malaysia - Yunus, Yusrina (2016)
The total flavonoid content and antioxidant activity are the properties of anti-cancer. The existence of the flavonoid content and antioxidant activity in plant shows that there are anti-cancer properties thus may reduce the cause of cancer among people. In this study, the total flavonoid content and antioxidant activity of five popular Malay raw salads were measured by using total flavonoid contents equivalents and DPPH free radical scavenging assay methods. The total flavonoid content was determined in each extract and quercertin is used as references standard to make calibration curve. Ranking order for total flavonoid content in the five plants in terms of quercertin equivalent were decreased in the order of B. Racemosa > S. Androgynus. > C. Gynandra > A. Occidentale > S. Palustris. The salads studied were the leaves of Stenochlaena Palustris (Pucuk Midin), Barringtonia Racemosa (Putat), Sauropus Androgynus (Cekur Manis), Cleome Gynandra (Maman), and Anacardium Occidentale (Pucuk Gajus). Meanwhile, the antioxidant activity of the plants was measured using DPPH radical scavenging assay with quercetin as positive control. Consequently, the DPPH scavenging effect of all extracts and standards on the DPPH radical decreased in the order of Quercertin > B. Racemosa > A. Occidentale > C. Gynandra > S. Palustris > S. Androgynus. Hence, the findings indicated promising antioxidant activity and total flavonoid content of aqueous extracts of these five traditional salads and B. Racemosa is found to have the highest total flavonoid content and antioxidant activity